2021
DOI: 10.3389/fcimb.2021.744013
|View full text |Cite
|
Sign up to set email alerts
|

The ERK-p38MAPK-STAT3 Signalling Axis Regulates iNOS Expression and Salmonella Infection in Senescent Cells

Abstract: The cellular changes occurring due to senescence like proliferation arrest, increase in free radical levels, and secretion of pro-inflammatory cytokines have been well studied, but its associated alteration in intracellular signalling networks has been scarcely explored. In this study, we examine the roles of three major kinases viz. p38 MAPK, ERK, and STAT3 in regulating iNOS expression and thereby the levels of the free radical Nitric oxide in senescent cells. Our study revealed that these kinases could diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…Fernandes et al. also demonstrated that MAP kinase/ERK rewired in senescent cells rendering them phenotypically different ( 65 ). Furthermore, studies implied that MAPK influenced cell survival in the endometrium ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al. also demonstrated that MAP kinase/ERK rewired in senescent cells rendering them phenotypically different ( 65 ). Furthermore, studies implied that MAPK influenced cell survival in the endometrium ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric Oxide (NO) is one of the key anti‐bacterial free radicals generated enzymatically by inducible nitric oxide synthetase, whose levels increase in response to an infection (Nathan & Hibbs, 1991) as well as naturally during aging (Donato et al, 2007). It was also recently shown that in aged cells and animals, the bacterial burden can be controlled naturally by elevated free radicals, primarily nitric oxide or NO (Fernandes & Saini, 2021), thereby demonstrating that free radicals in the aged tissue microenvironment function as a protective barrier to infection.…”
Section: Aging and Oxidative Stressmentioning
confidence: 99%
“…Enhanced inflammation in the elderly also results in higher tissue injury and impairment of the immune system, further accelerating aging (Weyand & Goronzy, 2016). Recently, it was also shown that for many intracellular pathogens, reactive free radicals (RNS specifically) strengthen inflammatory and defense responses as they can limit the intracellular proliferation of bacterial cells probably by causing mutagenic DNA damage (Fernandes & Saini, 2021). In this article, we highlight the importance of examining and understanding the link between increased lifespan, age‐associated diseases, and the emergence of AMR.…”
Section: Introductionmentioning
confidence: 99%
“…Control of SASP expression through the enhanced translation of MAPK-activated protein kinase 2 (MAPKAPK2 or MK2) has also been reported ( 34 , 35 ). MK2 kinase is also activated upon stress through the activation of p38 mitogen-activated protein kinases (p38MAPK) and this promotes the activation of NF-κB ( 36 , 37 ). Tumor necrosis factor (TNF)-α induces phosphorylation of AK kinase, resulting in signal transducers and activators of transcription 3 (STAT3) phosphorylation that translocate to the nucleus, contributing to persistent NF-κB activation and enhanced SASP expression ( 36 ) also promoted by the PI3k/Akt pathway.…”
Section: Introductionmentioning
confidence: 99%